The Effect Of Using UV Plastic Shade And Soil Amendments In Suppressing The Presence Of Thrips Pests On Tomato Plants In Dry Land - Rauhul Husni, Ika; Sudirman, Sudirman (International Journal of Science, Technology & Management, 2025)
This study examined the control of thrips through technical culture on tomato plants by combining soil amendments and UV plastic shade. An experiment was conducted in dry land in Gumantar village, North Lombok Regency, from May to September 2024. This study tested three levels of soil amendments (without soil amendments, with chicken manure, and biochar) and two levels of shade (without shade and with UV plastic shade). The treatments were arranged factorially using a randomized block design with three replications. The population of thrips, both larvae and imago, and the intensity of thrips pest attacks were observed. The results showed an interaction between soil amendments and UV plastic shelters in suppressing the first instar larvae of thrips pests on young leaves. The soil amendment factor significantly affected the presence of first instar larvae on old and young leaves. The UV plastic shelter treatment had a significant impact on all observation parameters, namely thrips pest imago on old and young leaves, first instar larvae on old and young leaves, second instar larvae on old and young leaves, and the intensity of thrips pest attacks.